Pedagogia da alternância e(m) etnodesenvolvimento: realidade e desafios - OLIVEIRA, Assis da Costa (Universidade Federal do Rio Grande do Sul, 2022)
This article analyzes the implementation process of Pedagogy of Alternation in the degree course of Ethnodevelopment, hosted by the Federal University of Pará, Altamira campus, Brazil. Initially, it reflects on theoretical framework that ground the alternation in the perspective of ethnodevelopment and interculturality. Subsequently, it analyzes the educational gains from the adoption of the methodology, particularly in the scope of the relation between theory and practice, traditional knowledge with scientific knowledge, as well as the problems and challenges that its adoption generates in the management scope and in the teaching practice.